PERLINDUNGAN HUKUM KONSUMEN TERHADAP PERJANJIAN STANDAR DALAM TRANSAKSI JUAL BELI MELALUI E-COMMERCE DI INDONESIA BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Ibrahim, Anis (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
Consumer protection in transacting through internet media, how is the validity of the use of standard agreements in e-commerce buying and selling transactions in Indonesia based on the Law on Information and Electronic Transactions No. 11 of 2008, regarding this inability can be started from the fact that there is no specific definition for e-commerce within the framework of the ITE Law, because trade activities carried out electronically are understood as "electronic transactions". How is the legal protection for consumers based on Law No. 8 of 1999 concerning the Consumer Protection Law (UUPK). Technological advances have led to a virtual world of trade transactions through the internet (e-commerce). As well as consumer protection in transactions in buying and selling leads to the failure to meet sellers and buyers directly. A sale and purchase agreement agreement will usually be reached through the medium of term of use and sale term conditions or what is called a standard agreement that has been provided by the website merchant, and if an online consumer accepts the term of use and sales term conditions, then the consumer only needs to select the accept button and at that time an agreement is born between the website merchant and the online consumer. The research method used is normative juridical. The data collection technique used is a literature study. In the consumer law No. 8 of 1999, there is consumer protection.